2011
DOI: 10.1055/s-0031-1291543
|View full text |Cite
|
Sign up to set email alerts
|

Learning, techniques, and complications of endoscopic ultrasound (EUS)-guided sampling in gastroenterology: European Society of Gastrointestinal Endoscopy (ESGE) Technical Guideline

Abstract: This article is the second of a two-part publication that expresses the current view of the European Society of Gastrointestinal Endoscopy (ESGE) about endoscopic ultrasound (EUS)-guided sampling, including EUS-guided fine needle aspiration (EUS-FNA) and EUS-guided Trucut biopsy. The first part (the Clinical Guideline) focused on the results obtained with EUS-guided sampling, and the role of this technique in patient management, and made recommendations on circumstances that warrant its use. The current Techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
264
3
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(288 citation statements)
references
References 148 publications
(157 reference statements)
7
264
3
14
Order By: Relevance
“…Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 . In our study, EUS-FNA using a 25-gauge needle was successfully performed in all of the pancreatic lesions, not just lesions in the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared the performance characteristics of a 22-gauge needle with those of a 25-gauge FNA needle for sampling pancreatic masses, but most have failed to demonstrate superiority of either needle [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . A recent systematic review and meta-analysis of EUS-FNA for solid pancreatic masses, including a large cohort of patients, revealed that a 25-gauge needle was more sensitive than a 22-gauge needle 23 . In our study, EUS-FNA using a 25-gauge needle was successfully performed in all of the pancreatic lesions, not just lesions in the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger specimens are sometimes required for the histological diagnosis of other pancreatic tumors 27,28 . In fact, 90% of specimens obtained using a 25-gauge needle and HNP were adequate for histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In experienced centers, the complication rate is <1%. 5 The adoption of EUS-FNA as a valuable diagnostic tool is not universal because of the reported risk of mucin spillage and peritoneal contamination during the procedure by some 6,7 and because of the lack of expertise in both the procedure and cytologic interpretation by others. 8 Given the shift in patient management toward conservative, nonsurgical management in a large percentage of patients with pancreatic cysts, 9-11 the added value of cyst fluid analysis is important.…”
Section: Introductionmentioning
confidence: 99%
“…Data are limited from randomized controlled trials comparing EUS-FNA to EUS-FNB in non-pancreatic mass lesions. [35,36] The published diagnostic yield of EUS-FNA for gastric subepithelial masses ranges from 42 % to 92 % [37,38]. Recently, Kim et al conducted a randomized controlled trial of 22 patients with gastric subepithelial tumors.…”
Section: Discussionmentioning
confidence: 99%